Mass and Lord's supper a study in the history of the liturgy - Lietzmann, Hans 1875-1942; Reeve, Dorothea H. G.; Richardson, Robert Douglas (Leiden E.J. Brill, 1979)
Part. 1. Mass and Lord's Supper -- Part. 2. A further inquiry into eucharistic origins with special reference to New Testament problems
Enthält bibliographsche Nachweise und Register
Massenentsäuert
Keywords: Liturgies, Early Christian; Lord's Supper (Liturgy)